Glycoside-metabolizing oxidoreductase D3dgpA from human gut bacterium - Kim, Heji; Mi, Huynh Thi Ngoc; Ahn, Joong-Hoon; Lee, Jong Suk; Eser, Bekir Engin; Choi, Jongkeun; Han, Jaehong (Frontiers in Bioengineering and Biotechnology, 2024)
The Gfo/Idh/MocA family enzyme DgpA was known to catalyze the regiospecific oxidation of puerarin to 3"-oxo-puerarin in the presence of 3-oxo-glucose. Here we discovered that D3dgpA, dgpA cloned from human gut bacterium Dorea sp. MRG-IFC3, was able to catalyze the regiospecific oxidation of various C-/O-glycosides, including puerarin, in the presence of methyl β-D-3-oxo-glucopyranoside. While C-glycosides were converted to 3"-and 2"-oxo-products by D3dgpA, O-glycosides resulted in the formation of the aglycones and hexose enediolone from the 3"-oxo-products. From the DFT calculations, it was found that isomerization of 3"-oxo-puerarin to 2"-oxo-puerarin required small activation energy of 9.86 kcal/mol, and the O-glycosidic bond cleavage of 3"-oxo-products was also thermodynamically favored with a small activation energy of 3.49 kcal/mol. In addition, the reaction mechanism of D3dgpA was discussed in comparison to those of Gfo/Idh/MocA and GMC family enzymes. Robust reactivity of D3dgpA was proposed as a new general route for the derivatization of glycosides.